Critical appraisal of the 2020 ESC guideline recommendations on diagnosis and risk assessment in patients with suspected non-ST-segment elevation acute coronary syndrome - Giannitsis, Evangelos; Blankenberg, Stefan; Christenson, Robert H.; Frey, Norbert; Haehling, Stephan von; Hamm, Christian; Inoue, Kenji; Katus, Hugo; Lee, Chien-Chang; McCord, James; Möckel, Martin; Chieh, Jack Tan Wei; et al. (Clinical research in cardiology, 2021)
Multiple new recommendations have been introduced in the 2020 ESC guidelines for the management of acute coronary syndromes with a focus on diagnosis, prognosis, and management of patients presenting without persistent ST-segment elevation. Most recommendations are supported by high-quality scientific evidence. The guidelines provide solutions to overcome obstacles presumed to complicate a convenient interpretation of troponin results such as age-, or sex-specific cutoffs, and to give practical advice to overcome delays of laboratory reporting. However, in some areas, scientific support is less well documented or even missing, and other areas are covered rather by expert opinion or subjective recommendations. We aim to provide a critical appraisal on several recommendations, mainly related to the diagnostic and prognostic assessment, highlighting the discrepancies between Guideline recommendations and the existing scientific evidence.
Gesehen am 24.07.2023